Government's Role in Empowerment Industrial Community Based on Creative Economy in Lampung Province in Islamic Economic Perspective - Budimansyah Budimansyah; diah mukminatul hasimi (ITB AAS INDONESIA Surakarta, 2022)
The formulation of the problem in this research are (1) What is the role of the government in empowering the creative economy-based industrial community in Lampung Province, (2) What is the form of government efforts in empowering the creative economy-based industry community in Lampung Province, (3) What is the government's role in community empowerment creative economy-based industry in Lampung Province in the perspective of Islamic economics?.The aims of this study are (1) to determine the role of the government in empowering the creative economy-based industrial community in Lampung Province, (2) to find out how the government's efforts are in empowering the creative economy-based industry community in Lampung Province, (3) to find out how the role of the government is in empowering the creative economy-based industry in Lampung Province. government in empowering the creative economy-based industrial community in Lampung Province in the perspective of Islamic economic. This research is a qualitative research with data collection techniques of observation, in-depth interviews and documentation. Informants in this study are local governments and creative economic entrepreneurs. The data used are primary and secondary data obtained from observations and from the archives of the relevant Department. Based on the results of the study, it can be concluded that the government of the Lampung Province has carried out Creative Economy empowerment activities in several stages; increasing awareness and capacity training, providing assistance, marketing (promotions) and capital loans. These activities are going well, but what happens in the field of related agencies is very lack of supervision, causes problems among business groups. The Islamic economic perspective in the implementation of creative economic empowerment is that there is injustice in the distribution of aid. This is not in accordance with the principles of Islamic economics, distribution justice.The conclusion of this study is that the empowerment of the creative economy is good enough, but the government’s supervision in the distribution of aid is very lack. It causies social jealousy among group members which is not in accordance with the principles of Islamic economic.